2009
DOI: 10.1038/ismej.2009.13
|View full text |Cite
|
Sign up to set email alerts
|

Actinorhodopsin genes discovered in diverse freshwater habitats and among cultivated freshwater Actinobacteria

Abstract: Microbial rhodopsins are membrane proteins that utilize a retinal chromophore to harvest sunlight for energetic and photosensory functions. Recently, a group of novel rhodopsin sequences named 'actinorhodopsins' (ActRs) was hypothesized to exist among uncultured planktonic Actinobacteria. ActRs were discovered by mining metagenomic data obtained during the Venter Institute's Global Ocean Sampling expedition, from a hypersaline lagoon, two estuaries and a freshwater lake. On the basis of these findings, and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(149 citation statements)
references
References 35 publications
7
142
0
Order By: Relevance
“…The latter possibility is contradicted by the apparent inability of acI to utilize carboxylic acids (see above), a major product of photochemical DOC reactions. Instead, previous work suggested that actinorhodopsins are broadly distributed in freshwater Actinobacteria and provide the potential for phototrophy (Sharma et al, 2008(Sharma et al, , 2009Martinez-Garcia et al, 2012;Garcia et al, 2013;Salka et al, 2014). We confirmed the presence of actinorhodopsin in all but three of the eleven acI SAGs (AAA023-J06, AAA028-A23 and AB141-P03) making this gene a likely part of the broadly shared genes of the acI lineage.…”
Section: Ecogenomics Of the Aci Lineagesupporting
confidence: 70%
See 1 more Smart Citation
“…The latter possibility is contradicted by the apparent inability of acI to utilize carboxylic acids (see above), a major product of photochemical DOC reactions. Instead, previous work suggested that actinorhodopsins are broadly distributed in freshwater Actinobacteria and provide the potential for phototrophy (Sharma et al, 2008(Sharma et al, , 2009Martinez-Garcia et al, 2012;Garcia et al, 2013;Salka et al, 2014). We confirmed the presence of actinorhodopsin in all but three of the eleven acI SAGs (AAA023-J06, AAA028-A23 and AB141-P03) making this gene a likely part of the broadly shared genes of the acI lineage.…”
Section: Ecogenomics Of the Aci Lineagesupporting
confidence: 70%
“…We identified the top 25 COGs that are overrepresented in the acI SAGs as compared with the 424 Actinomycetales reference genomes available in the IMG database in March 2013 (Table 3). Bacteriorhodopsin (COG5524) was the most overrepresented COG in this analysis, and represents the putative light-harvesting protein previously identified as actinorhodopsin (Sharma et al, 2008(Sharma et al, , 2009Martinez-Garcia et al, 2012;Wurzbacher et al, 2012). The aforementioned cyanophycinase (COG4242) was another COG overrepresented in the acI lineage.…”
Section: Ecogenomics Of the Aci Lineagementioning
confidence: 92%
“…Six primer pairs from Koh et al (2010) were used in combination with a seventh pair using the additional reverse primer (Supplementary Information; Table 1). It should be noted that sequences representative of the actinorhodopsin-like LG1 and LG2 groups (Sharma et al, 2008(Sharma et al, , 2009) present a TWXXYP region at the 3 0 end and would not be amplified by our set of reverse primers that are based on GWXXYP (Atamna-Ismaeel et al, 2008) and SWXFY regions. PCRs were performed with the hot start Platinum Taq DNA Polymerase (Invitrogen, Madrid, Spain).…”
Section: Pr Primers and Pcr Amplificationmentioning
confidence: 99%
“…Although degenerate primers can capture a wide range of PRs, other types of microbial rhodopsins may not be amplified (see Materials and Methods section). For example, our primers did not target a diverse group of rhodopsins, the actinorhodopsins, associated with Actinobacteria (Sharma et al, 2008(Sharma et al, , 2009.…”
Section: Winter Patterns In Pr Diversitymentioning
confidence: 99%
“…The initial publication ) analyzed 44 metagenome samples (0.1-0.8 mm fraction) collected from 41 sites, including Sargasso Sea sites examined previously by Venter et al (2004). Data from these locations have been analyzed to reveal an immense set of novel proteins and breadth of taxonomic and functional diversity in different habitats Yutin et al 2007;Zhang and Gladyshev 2008;Sharma et al 2009). …”
Section: Taxonomic Diversity From the Global Ocean Sampling Expeditionmentioning
confidence: 99%